1978
DOI: 10.1093/ajcp/69.4.446
|View full text |Cite
|
Sign up to set email alerts
|

Scleromyxedema Myopathy: Histochemical and Electron Microscopic Observations

Abstract: A biopsy-proven case of scleromyxedema (papular mucinosis) with IgG lambda light chain paraproteinemia, eosinophilia and severe proximal myopathy is presented. Muscle biopsy revealed an atypical necrotizing vacuolar myopathy. Histochemical studies of cryostat sections revealed fiber necrosis, severe type II fiber atrophy, and fiber vacuolization with NADH tetrazolium reductase hyperactivity. Electron microscopy showed myocytolysis, reduplication of the basement membrane, and unit membrane-lined vacuoles negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Verity et al . reported that this myopathy shared histopathological features with DM; 2 however, no photosensitivity, heliotrope erythema, erythema of the dorsum of the hands, Gottron's papules or antinuclear antibodies suggestive of DM have been described in association with this scleromyxedema‐associated myopathy, which is therefore probably a distinct entity. Fourthly, a real association between scleromyxedema and DM has only exceptionally been reported 6,7 .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Verity et al . reported that this myopathy shared histopathological features with DM; 2 however, no photosensitivity, heliotrope erythema, erythema of the dorsum of the hands, Gottron's papules or antinuclear antibodies suggestive of DM have been described in association with this scleromyxedema‐associated myopathy, which is therefore probably a distinct entity. Fourthly, a real association between scleromyxedema and DM has only exceptionally been reported 6,7 .…”
Section: Discussionmentioning
confidence: 83%
“…However, this mucinosis is rarely clinically detectable; 13–15 it is typically a secondary mucinosis whose pathogenesis remains unclear but probably involves fibroblast stimulation by cytokines such as interleukin‐1 or interferon 16,17 . Thirdly, scleromyxedema can be associated with a myopathy that differs from DM 2–5 . Usually, scleromyxedema‐associated myopathy occurs months or even years after the onset of scleromyxedema but myopathy preceding scleromyxedema has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…7,17,18 Other reports of successful treatment include granulocyte colonystimulating factor, 19 plasmapheresis, 20 external beam irradiation, 21 intravenous immunoglobulin, 22 interferon alfa2a, 23 and extracorporal photopheresis. 24 Multiple chemotherapeutic agents have been used, including melphalan, 5,25,26 cyclosporine, 27 cladribine, 28 cyclophosphamide, 29,30 methotrexate, 31,32 and chlorambucil. 33 Despite all these reported trials, most patients with scleromyxedema do not show a significant response to therapy.…”
Section: Commentmentioning
confidence: 99%
“…Reported treatments include systemic retinoids, [17][18][19] corticosteroids (including dexamethasone 20 ), adrenocorticotropic hormone, 12 interferon), 22 2-chlorodeoxyadenosine, 23 granulocyte colony-stimulating factor, 24 thalidomide, 4 plasmapheresis, 25,26 dermabrasion, 27 electron beam radiation, 28 extracorporeal photochemotherapy, 29 and PUVA. 30 Other agents, including melphalan, 31-33 cyclophosphamide, 34 cyclosporine, 35-37 methotrexate, 38,39 and chlorambucil, 40 have been used with some success but are limited by toxicity. Prednisone has also been used successfully: Rayson et al 41 reported a case of a 40-year-old woman with scleromyxedema associated with a monoclonal IgG-lambda and with severe cutaneous and systemic manifestations.…”
Section: Discussionmentioning
confidence: 99%